The Legal Dimensions of Genomic Sequencing in Newborn Screening - Zacharias, Rachel L. (The Hastings Center report, 2018)
The possible integration of genomic sequencing (including whole-genome and whole-exome sequencing) into the three contexts addressed in this special report—state-mandated screening programs, clinical care, and direct-to-consumer services—raises related but distinct legal issues. This essay will outline the legal issues surrounding the integration of genomic sequencing into state newborn screening programs, parental rights to refuse and access sequencing for their newborns in clinical and direct-to-consumer care, and privacy-related legal issues attending the use of sequencing in newborns.